Relationship between fertility traits and kinematics in clusters of boar ejaculates - Barquero, Vinicio; Roldan, Eduardo R. S.; Soler, Carles; Vargas-Leitón, Bernardo; Sevilla, Francisco; Camacho, Marlen; Valverde-Abarca, Anthony (Biology, 2021)
Swine reproduction efficiency is determined by the fertility potential of the sow and sperm quality. The objective of this study is to compare boar sperm motility and kinematic features to evaluate their relationships with reproductive success after artificial insemination (AI). In this study, the movement patterns of boar ejaculates were analyzed by a computer-assisted semen analysis (CASA)-Mot system, and the kinematic values of ejaculate clusters were assessed. The semen of the Pietrain boars showed more linear trajectory of the spermatozoa, while curvilinear velocity and oscillatory movement characterized the semen of the Duroc × Pietrain boars. The offspring of sows inseminated with Pietrain boars showed significantly lower number of stillbirths. In addition, ejaculate grouping into clusters did not have a predictive capacity on litter size variables. Nevertheless, the kinematic variables of the ejaculate may have a predictive, albeit reduced, capacity regarding litter size variables. The results of this study therefore open up possibilities for future assessments of fertility
Casa -- Programa para computador
Biology, vol. 10, no.7 (Jun, 2021)
Keywords: Cerdos; Calidad del esperma; Espermatozoides - Motilidad; Casa -- Programa para computador; Inseminación artificial